Blending type approximation by τ-Baskakov-Durrmeyer type hybrid operators - Mohiuddine, S. A.; Kajla, Arun; Mursaleen, M.; Alghamdi, Mohammed A. (Advances in difference equations, 2020)
In this work, we construct a Durrmeyer type modification of the τ -Baskakov operators depends on two parameters α > 0 and τ ∈ [ 0 , 1 ] . We derive the rate of approximation of these operators in a weighted space and also obtain a quantitative Voronovskaja type asymptotic formula as well as a Grüss Voronovskaya type approximation.